Hollow and sulfonated microporous organic polymers: versatile platforms for non-covalent fixation of molecular photocatalysts1. Issue 58 (25th June 2015) - Park, Nojin; Kang, Daye; Ahn, Min Cheol; Kang, Sungah; Lee, Sang Moon; Ahn, Tae Kyu; Jaung, Jae Yun; Shin, Hee-Won; Son, Seung Uk
<x xml:space="preserve">Abstract</x> Sulfonated hollow microporous organic polymers showed excellent heterogenization ability towards various cationic photocatalysts through ionic interaction.